2012
DOI: 10.1590/s0103-21002012000400006
|View full text |Cite
|
Sign up to set email alerts
|

O cuidador e a sobrecarga do cuidado à saúde de pacientes egressos de internação psiquiátrica

Abstract: Objective: To identify the sociodemographic characteristics and the level of burden on family caregivers of patients discharged from psychiatric hospitalization. Methods: A quantitative exploratory study, performed in an outpatient mental health setting, using a questionnaire and the Burden Assessment Scale for Families. The sample was composed of 21 caregivers of patients discharged from psychiatric hospitalization. Results: All caregivers had a family relationship, the mean age was 46 years, of whom the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
18

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 9 publications
2
9
0
18
Order By: Relevance
“…The socio-demographic profile of the participants of this study confirmed results of previous studies [8,9], and the study sample consisted of subjects with low education and aged between 30 and 60 years old. The primary family caregiver role reflected significantly in females, especially in mothers and grandmothers.…”
Section: Discussionsupporting
confidence: 84%
“…The socio-demographic profile of the participants of this study confirmed results of previous studies [8,9], and the study sample consisted of subjects with low education and aged between 30 and 60 years old. The primary family caregiver role reflected significantly in females, especially in mothers and grandmothers.…”
Section: Discussionsupporting
confidence: 84%
“…Os grupos de família oferecem a possibilidade de os familiares elaborarem seus sofrimentos e pensarem juntos sobre estratégias singulares para lidarem com o sofrimento psíquico em suas vidas. Essa atividade, comum em serviços de saúde mental, é considerada instrumento poderoso para a autorreflexão, educação em saúde mental, e criação de vínculos entre serviço e família, sendo muito valorizada em diversas pesquisas 19 Essa articulação entre equipamentos de saúde mental e família está ainda em desenvolvimento e apresenta fragilidades, como: falta de profissionais preparados para lidar com essa demanda, excesso de atendimentos para os trabalhadores, falta de recursos dos serviços de saúde mental, e falta de entendimento ou conhecimento, pelos familiares, das novas propostas da saúde mental 7 . A inserção da família não foi efetivada completamente nos serviços substitutivos, e só se dá importância a esse aspecto quando se foca em ações para o usuário.…”
Section: Resultados E Discussão 1) Família E Serviçounclassified
“…Segundo Borba et al 6 , ao se identificar a percepção da família com relação ao sofrimento psíquico, à pessoa e ao seu cuidado, pode-se concluir que lidar com família é lidar com sofrimento. Entretanto, os familiares não estão habituados a falar sobre a dimensão subjetiva, relacionada a sentimentos, preocupações e percepção da experiência de conviver com o sofrimento psíquico 7 . Para esses familiares, essa dimensão pode ser algo novo, pois, antes, era vista como causa da doença, da qual deveriam se distanciar; mas, atualmente, a participação deles no cuidado é requisitada.…”
Section: Introductionunclassified
“…encircles the sociocultural vestiges of an extremely maledominated society, which historically exclude male subjects with the role of caring for someone in certain scenarios, since women, in most societies, have always assumed this function. [15] Being a doula, in fact, particularly in Northeastern Brazil, means exploring the possibilities and demystifying taboos. Many of which historically built and entrenched in our society.…”
Section: Discussionmentioning
confidence: 99%